Evaluation of Ionizing Radiation Protection among Radiation Workers in X-ray departments in Erbil City - Runak T. Ali; Safa M. Hameed; Qasim A. Ali (مجلة كلية الطب, 2016)
Background: Ionizing radiations are hazardous agents in the workplace, since all forms of ionizing radiation produce some type of injury that is incurable. Therefore, protection against ionizing radiation exposure can play an important role in the health of workers. Objectives: is to evaluate the application of radiation protection among radiation workers at X-ray department in Erbil hospitals. Patients and methods: Six hospitals (General and Private) were visited. Samples of 110 were randomly selected among 135 radiation workers, 47 (42.3%) female and 63 (57.3%) male Data was collected through structured questionnaires. The surveyed data was coded and analyzed by using MS Excel software, and SPSS 18 for analysis. Analysis was performed by means of frequency distributions and cross tabulations. Results: The results showed that there are majority of the workers 51 (46.4%) aged between 21 - 30 years, and Diploma holders 68 (61.8%). Only 49 (44.5%) undergone primary examination while 47 (42.7%) never done periodical examination. According to international commotion of radiation protection regulation of radiation protection, it is mandatory for radiation workers to wear personal detective devices during work. But a large numbers 89 (80.9%) have not supplied with such devices. The study also revealed that the majority of workers were engaged in work beyond 40 hours per week. Calibration of the X-rays machine and radiation survey of the work place have not been regularly done. Only 30 of the sample have no awareness and knowledge about the ionizing radiation, while 95 (86.4%) have no healthy advice. Conclusion: It can be suggested that the level of workers education must be increased and short courses be implemented such as dosimetery and radiation protection performance.